Strategi Komunikasi Pemasaran KDK Matahari UHAMKA dalam Membangun Brand Awareness - Junita, Junita Holifah; Rahmawati, Yulia; Fadilah, Aulia; Pramestia, Reka Ardiyana; Putra, Gilang Kumari (Brand Communication, 2023)
This paper describes the marketing communication strategy carried out by KDK Matahari UHAMKA in building its brand awareness. In this study using a qualitative approach with a descriptive type of research. Determination of informants in this study using purposive sampling technique meaning by using case study research methods, data collection methods direct observation in the field, in-depth interviews, personal documents, reference books, several journals and the internet and using data processing with triangulation techniques. . The results showed that KDK Matahari UHAMKA used a marketing communication strategy of STP (Segmentation, Targeting, and Positioning) in order to identify market groups before implementing a marketing communication strategy. However, in carrying out its communication strategy, KDK Matahari UHAMKA has shortcomings in terms of building communication between management and members, the lack of maximizing the use of marketing through digital platforms, and also currently the business being carried out is only within the UHAMKA environment.